A Study of Matthayomsuksa 3 Students’ Learning Achievement of The Unit on “Economic Integration” Through Jigsaw Technique Cooperative Learning With Mind Mapping and Their Teamwork Behaviors - ปรางสุข, รดาการ; จุลศิริพงษ์, สิทธิศักดิ์ (Ratchaphruek Journal, 2018)
The purposes of this research were 1) to compare students’ learning achievement before and after study learning the unit on “Economic Integration” using the 70 percent criterion and 2) to compare the teamwork behaviors scores of students before and after the jigsaw technique cooperative learning with mind mapping. The sample were 48 Matthayomsuksa 3/1 students in 2nd semester of 2016 academic year at Nongkipittayakom School, Nongki District, Buriram Province, Secondary Education Service Office 32. The research instruments consisted of 4 lesson plans of the unit, the achievement tools and the observation form for teamwork behaviors. The data were analyzed using percentage, mean ( ), (S.D.) and t-test (t-test for dependent samples) The results of the study were as follows: 1. The average score in learning achievement pretest was 14.02 at 46.73% and the posttest was 23.31 at 77.70% which represented the average progress score of 9.29 at 30.97%. So, the score in learning achievement posttest was higher than the 70% criterion and significantly higher than the pretest at .05 levels. 2. The students’ average scores of teamwork behaviors before the cooperative Learning was 24.76 at 68.78% and after the cooperative learning was 32.30 at 89.73% which represented the progress score of 7.54 at 20.95%. So, the average score of teamwork behaviors after jigsaw technique cooperative learning with mind mapping was significantly higher at .05 levels. The jigsaw technique cooperative learning with mind mapping should be encouraged for continuous use.